Efeitos de um programa preventivo de orientação parental com base em práticas positivas: coletânea de casos - Rodrigues, Márcia Ferreira da Silva (2019)
The relationship between parents and children affects the course of the child's development. By improving the repertoire of parental skills and practices, parents are more likely to be able to help their child develop adaptive behaviors and also to deal with their child maladaptive behaviors. This study adapted a program of positive parenting practices for the purpose of developing the parental skills repertoire. The objective was to analyze the feasibility of applying this program and to verify its effect on child behavior problems and parental social skills. The design chosen for the present study was case collection. A total of 115 primary caregivers of children three to five years of age attending a private educational institution were invited to participate. Preand post-treatment evaluation was carried out with the "Child Behavior Checklist for age 1.5 to 5" (CBCL/1.5-5) and the "Roteiro de Entrevista de Habilidades Socias Educativas Parentais" (RE-HSE-P). Besides, at the end of the program, participants answered a questionnaire about their satisfaction with the treatment. Results indicated low interest of the parents to participate in a preventive program, with only six of the 115 invited parents starting (5.22%) and four completing all stages of the program (3.48%). Among the mothers who participated, there were deficits in the use of positive socio-educational practices, with scores in the clinical or borderline range in the scales of the RE-HSE-P. After participating in the program, there was a decrease in negative educational practices, but no changes in the parental educational social skills. Although not all children had problems in the borderline or clinical range of CBCL/1.5-5, there was a reduction in behavioral difficulties in the final assessment. It is discussed the difficulties of implementing universal preventive strategies in de community. We understand that it is necessary to develop strategies to attract parents/caregivers to participate in preventive actions, so that it is feasible to guide families in the development of educational social skills and on the importance of using positive parental practices before the emotional and behavioral difficulties are established in the child repertoire.